From design to applications of stimuli-responsive hydrogel strain sensors - Zhang, Dong; Ren, Baiping; Zhang, Yanxian; Xu, Lijian; Huang, Qinyuan; He, Yi; Li, Xuefeng; Wu, Jiang; Yang, Jintao; Chen, Qiang; Chang, Yung; Zheng, Jie (Journal of materials chemistry. B, Materials for biology and medicine, 2020)
Stimuli-responsive hydrogel strain sensors that synergize the advantages of both soft-wet hydrogels and smart functional materials have attracted rapidly increasing interest for exploring the opportunities from material design principles to emerging applications in electronic skins, health monitors, and human-machine interfaces. Stimuli-responsive hydrogel strain sensors possess smart and on-demand ability to specifically recognize various external stimuli and convert them into strain-induced mechanical, thermal, optical, and electrical signals. This review presents an up-to-date summary over the past five years on hydrogel strain sensors from different aspects, including material designs, gelation/fabrication methods, stimuli-responsive principles, and sensing performance. Hydrogel strain sensors are classified into five major categories based on the nature of the stimuli, and representative examples from each category are carefully selected and discussed in terms of structures, response mechanisms, and potential medical applications. Finally, current challenges and future perspectives of hydrogel strain sensors are tentatively proposed to stimulate more and better research in this emerging field. Stimuli-responsive hydrogel strain sensors that synergize the advantages of both hydrogel and smart functional materials have attracted increasing interest from material design to emerging applications in health monitors and human-machine interfaces.